A study of the relationship between social support, depression, alexithymia and glycemic control in patients with type 2 diabetes mellitus: a structural equation modeling approach - Gan, Yuqin; Tian, Fengxiang; Fan, Xinxin; Wang, Hui; Zhou, Jian; Yang, Naihui; Qi, Hong (Frontiers in Endocrinology, 2024)
The aim of this research was to ascertain the correlations between alexithymia, social support, depression, and glycemic control in patients diagnosed with type 2 diabetes mellitus. Additionally, this study sought to delve into the potential mediating effects of social support and depression in the relationship between alexithymia and glycemic control.Method A purposive sampling methodology was employed to select a cohort of 318 patients afflicted with type 2 diabetes mellitus, hailing from a care establishment situated in Chengdu City.This investigation embraced a cross-sectional framework, wherein instruments such as the General Information Questionnaire, the Toronto Alexithymia Scale 20, the Social Support Rating Scale, and the Hamilton Depression Scale were judiciously administered. The primary objective of this endeavor was to unravel the interplay that exists amongst alexithymia, social support, depression, and glycemic control. The inquiry discerned these interrelationships through both univariate and correlational analyses, subsequently delving into a comprehensive exploration of the mediating ramifications engendered by social support and depression in the nexus between alexithymia and glycemic control.The HbA1c level of patients diagnosed with type 2 diabetes mellitus was recorded as (8.85±2.107), and their current status with regards to alexithymia, social support, and depression were measured as (58.05±4.382), (34.29±4.420), and (7.17±3.367), respectively. Significant correlations were found between HbA1c and alexithymia (R=0.392, P<0.01), social support (R=-0.338, P<0.01), and depression (R=0.509, P<0.01). Moreover, alexithymia correlation with social support (R=-0.357, P<0.01) and with depression (R=0.345, P<0.01). Regarding the mediation analysis, the direct effect of alexithymia on HbA1c was calculated to be 0.158, while the indirect effect through social support and depression were 0.086 and 0.149, respectively. The total effect value was determined to be 0.382, with the mediating effect accounting for 59.95% , and the direct effect accounting for 40.31%.Alexithymia exerts both direct and indirect adverse effects on glycemic control, thereby exacerbating disease outcomes. Hence, it is imperative to prioritize the mental health status of individuals with type 2 diabetes to enhance overall well-being, ameliorate diabetes-related outcomes, elevate patients' quality of life, and alleviate the psychological distress and financial burden associated with the condition.